Estudo dos efeitos do ataque ácido nas propriedades química, mineralógica e morfológica de geomateriais - Ferrazzo, Suéllen Tonatto (2018)
Exposure of sandy, silty and clayey geomaterials with acid leachates can result in dissolution of metals, desorption of chemical species, partial dissolution of minerals, affecting their physical and chemical properties. In the literature, it is also identified the need to evaluate the alterations of geomaterials properties, in a pure state and in extreme acid conditions. Thus, this study aimed to evaluate the chemical, mineralogical and morphological properties of the Osorio Fine Uniform Sand (OFS), Basalt Residual Soil (BRS), Kaolin (KAO) and Bentonite (BEN), and changes in the physical-chemical composition of the resulting liquid extracts. The materials were submitted to solutions of sulfuric acid on concentrations of 0.00, 0.01 and 1.00 mol/L. The experiments were conducted in a manner adapted to the batch test methodology of ASTM D4646-03. Samples were characterized by X-ray fluorescence, X-ray diffraction, thermogravimetry and differential scanning calorimetry and scanning electron microscopy. The liquid extracts determined the concentration of Na, Mg, Al, K, Ca, Fe and Mn by inductively coupled plasma atomic emission spectrometry, pH and electrical conductivity. Exposure to the H2SO4 0.01 mol/L solution did not cause changes in the characteristics of the geomaterials evaluated. However, the contact with the solution of 1.00 mol/L of H2SO4 has resulted in reduction of the main constituents oxides, loss of some minerals, formation of sulfate minerals, as well as alteration of the peak of water dehydration in the pores and loss mass. Particles morphology of the sand and bentonite particles of geomaterials appears does not to have undergone alterations from the acid exposure. However, acid attack resulted in changes in the particles surface of basalt residual soil and kaolin. The results of pH and electrical conductivity of the liquid extracts indicate the good acid buffering capacity of the bentonite submitted at 0.01 mol/L H2SO4, and a higher dissolution of ions with increasing acid concentration. The contact with H2SO4 1.00 mol/L resulted in the metal constituents solubilization, corresponding to reductions in the elemental composition and changes in the mineralogy of the geomaterials.